ENHANCING CLASSROOM ENGAGEMENT THROUGH IOT-ENABLED SMART LEARNING ENVIRONMENTS - Mohanty, Akshaya Kumar; kumar, S V Anil; Thongam, Rabichand; Kawale, Sheetalrani R; Jakkani, Anil Kumar; V G, Vani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper investigates the impact of Internet of Things (IoT)-enabled Smart Learning Environments on student engagement in educational settings. The integration of IoT technologies aims to enhance traditional teaching methods by providing interactive and personalized learning experiences. Through a mixed-methods research approach, data were collected from both teachers and students before and after the implementation of IoT tools in the classroom. Results indicate a significant increase in student engagement levels, with a rise from 60% to 85% post-implementation, reflecting enhanced participation, attention, and interaction. Comparative analysis reveals that IoT-enhanced learning environments foster greater collaboration and efficiency in completing tasks. The study further discusses the implications of these findings in relation to existing literature on technology in education, highlighting the positive correlation between IoT integration and improved academic performance. Challenges encountered during the implementation, such as technical issues and resistance from educators, are also addressed.